An outbreak of SARS-CoV-2 with high mortality in mink (Neovison vison) on multiple Utah farms - Chrissy D. Eckstrand (Public Library of Science (PLoS), 2021)
The breadth of animal hosts that are susceptible to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and may serve as reservoirs for continued viral transmission are not known entirely. In August 2020, an outbreak of SARS-CoV-2 occurred on five mink farms in Utah and was associated with high mink mortality (35–55% of adult mink) and rapid viral transmission between animals. The premise and clinical disease information, pathology, molecular characterization, and tissue distribution of virus within infected mink during the early phase of the outbreak are provided. Infection spread rapidly between independently housed animals and farms, and caused severe respiratory disease and death. Disease indicators were most notably sudden death, anorexia, and increased respiratory effort. Gross pathology examination revealed severe pulmonary congestion and edema. Microscopically there was pulmonary edema with moderate vasculitis, perivasculitis, and fibrinous interstitial pneumonia. Reverse transcriptase polymerase chain reaction (RT-PCR) of tissues collected at necropsy demonstrated the presence of SARS-CoV-2 viral RNA in multiple organs including nasal turbinates, lung, tracheobronchial lymph node, epithelial surfaces, and others. Localization of viral RNA by in situ hybridization revealed a more localized infection, particularly of the upper respiratory tract. Whole genome sequencing from multiple mink was consistent with published SARS-CoV-2 genomes with few polymorphisms. The Utah mink SARS-CoV-2 strains fell into Clade GH, which is unique among mink and other animal strains sequenced to date. While sharing the N501T mutation which is common in mink, the Utah strains did not share other spike RBD mutations Y453F and F486L found in nearly all mink from the United States. Mink in the outbreak reported herein had high levels of SARS-CoV-2 in the upper respiratory tract associated with symptomatic respiratory disease and death. Author summary The recent emergence and spread of the novel coronavirus has resulted in worldwide disease and economic hardship. The virus, known as SARS-CoV-2 is believed to have originated in bats and has spread worldwide through human-to-human virus transmission. It remains unclear which animal species, other than humans, may also be susceptible to viral infection and could naturally transmit the virus to susceptible hosts. In this study, we describe the early phases of an outbreak of disease and death due to SARS-CoV-2 infection in farmed mink in Utah, United States. The investigation reveals that mink can spread the virus rapidly between animals and that the disease in mink is associated with viral infection and damage to tissues of the upper and lower respiratory system. The determination that mink are susceptible to SARS-CoV-2 indicates the need for strict biosecurity measures on mink farms to remediate mink-to-mink and human-to-mink transmission for the protection of mink, as well as prevent potential transmission from mink to humans. It may be prudent for humans working with SARS-CoV-2 mink to wear appropriate PPE until more is understood.